Geospatial techniques for comparative case study of spatiotemporal changes in New Karachi and North Karachi parks - Arif, Hiba; Kausar, Anila; Afzal, Ambreen; Ahmed, Samreen Riaz; Afsar, Sheeba; Lahori, Altaf Hussain; Vambol, Sergij; Vambol, Viola (Ecological Questions, 2023)
The well-known fact is that parks play a significant role in sustaining the urban environment. Megacities like Karachi are developing rapidly with a simultaneous increase in the city area, putting immense pressure on open green spaces. The widespread built-up development is replacing the previously existing vegetative cover. The lack of green spaces is the main concern, and this problem will only worsen due to overpopulation associated with the rapid growth of cities. The lack of evidence-based planning contributes to the unbalanced spatial distribution of parks in quantity and quality. The present research aimed to compare and find out the quality and status of parks such as park areas under encroachment and temporal changes in the vegetative cover of parks in the predominantly low to middle-income residential areas of New Karachi and North Karachi Towns of Karachi metropolitan. Geospatial techniques have been used for mapping, assessments, and analyses. Results indicate that boundary walls are a good solution to stop or reduce park encroachments as correlation indicates the parks with boundary walls have a significantly lower percentage of encroachment in 2022. The existing work indicated that the number of trees has increased in most parks in both towns in 2022. The overall correlation results indicate that factors affecting park quality positively have a positive association with other positively affecting factors and a negative association with factors that affect park quality negatively. There is a dire need to implement better planning strategies to enhance the quality of existing parks and construct new parks in the study area.